High Space-Time Resolution Observation of Extreme Orographic Rain Gradients in a Pacific Island Catchment - Benoit, L.; Lucas, M.; Tseng, H.; Huang, Y.-F.; Tsang, Y.-P.; Nugent, A. D.; Giambelluca, T. W.; Mariethoz, G. (Frontiers in Earth Science, 2021)
In the vicinity of orographic barriers, interactions between mountains and prevailing winds can enhance rainfall and generate strong spatial gradients of precipitation. Orographic rainfall is still poorly quantified despite being an important driver of headwater catchment hydrology, in particular when considered at high space-time resolution. In this paper, we propose a complete framework for the observation and quantification of orographic rainfall gradients at the local scale. This framework, based on the stochastic interpolation of drop-counting rain gauge observations, provides reconstructions of local rain fields at high space-time resolution. Such rain estimates can be used to investigate how rainfall gradients develop during rain storms, and to provide better input data to drive hydrological models. The proposed framework is presented in the form of a proof-of-concept case study aimed at exploring orographic rain gradients in Mānoa Valley, on the leeward side of the Island of Oʻahu, Hawaiʻi, USA. Results show that our network of eight rain gauges captured rainfall variations over the 6 x 5 km2 study area, and that stochastic interpolation successfully leverages these in-situ data to produce rainfall maps at 200 m x 1 min resolution. These maps are used to derive maps of rain accumulation, rain intermittency, as well as mean and peak rain intensity at the storm scale.